Kajian Hukum Islam tentang Wakaf Material dalam Pembangunan Masjid di Kabupaten Pidie - Zul Azimi (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2025)
This study aims to examine the culture of waqf among the community in Pidie Regency and to explore the practice of material waqf for mosque construction from the perspective of Islamic law. The research employed a qualitative method with a field study approach, where data were collected through interviews and observations. The findings reveal that waqf plays an important role as a social and economic instrument in Pidie, with the community actively contributing through productive and material waqf, especially for mosque construction. Despite challenges regarding the legal status of material waqf objects in Islamic law, the community continues to participate actively. Movable waqf assets, including cash waqf, are recognized for their greater flexibility and significant social and economic benefits. However, issues related to waqf management and the competence of waqf trustees (nadzir) remain concerns that need to be addressed through education and professional management.